2009
DOI: 10.1093/schbul/sbp095
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Cognitive Assessment Tool for Schizophrenia: Construction of a Tool for Clinicians

Abstract: Cognitive impairment in schizophrenia is often severe, enduring, and contributes significantly to chronic disability. But clinicians have difficulty in assessing cognition due to a lack of brief instruments. We evaluated whether a brief battery of cognitive tests derived from larger batteries could generate a summary score representing global cognitive function. Using data from 3 previously published trials, we calculated the corrected item-total correlations (CITCs) or the correlation of each test with the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 35 publications
(54 reference statements)
1
62
0
2
Order By: Relevance
“…Regarding decision validity, both scales showed good ability to differentiate between individuals with and without cognitive impairment in terms of a global measure of cognitive functioning. Hurford et al (2009) demonstrated that the B-CATS is a brief cognitive instrument composed of well-known cognitive subtests with adequate psychometric properties. In fact, it appears to be a good choice for screening cognitive impairment in schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding decision validity, both scales showed good ability to differentiate between individuals with and without cognitive impairment in terms of a global measure of cognitive functioning. Hurford et al (2009) demonstrated that the B-CATS is a brief cognitive instrument composed of well-known cognitive subtests with adequate psychometric properties. In fact, it appears to be a good choice for screening cognitive impairment in schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…Examples are the Brief Cognitive Assessment (BCA) (Velligan et al, 2004), the Screen for Cognitive Impairment in Psychiatry (SCIP) (Purdon, 2005); and the Brief Cognitive Assessment Tool for Schizophrenia (B-CATS) (Hurford et al, 2009). These all are simple and easy-to-administer instruments that require minimal additional equipment and have shown good psychometric properties (Guilera et al, 2009;Hurford et al, 2009;Pino et al, 2008;Purdon, 2005;Rojo et al, 2010;Velligan et al, 2004). Until their advent, there were no such instruments designed for detecting cognitive deficits in psychiatric disorders in only 15 min per patient.…”
Section: Schizophrenia Researchmentioning
confidence: 99%
“…The Brief Cognitive Assessment (BCA) (Velligan et al, 2004) and the Brief Cognitive Assessment Tool for Schizophrenia (B-CATS) (Hurford et al, 2011) have sound psychometric properties and good correlations with functional measures and can be completed in 15 minutes. The Brief Assessment of Cognition in Schizophrenia (BACS) battery has good psychometric properties, has alternate forms to minimise practice effects and the composite score relates strongly to functional measures (Keefe et al, 2006a).…”
Section: Psychological and Psychosocial Therapiesmentioning
confidence: 99%
“…A few short performance-based cognitive assessments, for example, the Brief Assessment of Cognition in Schizophrenia (BACS), the Brief Cognitive Assessment (BCA), and the Brief Cognitive Assessment Tool for Schizophrenia (B-CATS), have been developed to evaluate the general cognitive function in schizophrenia (Gold et al, 1999;Hurford et al, 2011;Keefe et al, 2004;Velligan et al, 2004). Nonetheless, the clinical usage, reliability or validity is not well established.…”
Section: Introductionmentioning
confidence: 99%